Possibilities to improve the antioxidative capacity of beer by optimized hopping regimes. Issue 4 (26th September 2014) - Kunz, T.; Frenzel, J.; Wietstock, P. C.; Methner, F.‐J.
<x xml:space="preserve">Abstract</x> Different hopping regimes were evaluated to investigate the effect on the oxidative stability of wort and beer. Compared with a single hop dosage at the beginning of wort boil, it was possible to increase the concentration of α‐acids in pitching wort and beer by applying incremental hop dosage, dry hopping or the use of a pre‐isomerized hop product in combination with an α‐acid extract, which concomitantly resulted in lower iron concentrations and an enhanced flavour stability as indicated by standard wort and beer analyses, atomic absorption spectroscopy, electron spin resonance spectroscopy and sensory analysis of fresh and force‐aged beers. The functional principle of hop dosage variations is explained by saving of α‐acids throughout the wort production process, which yields an increased formation and precipitation of pro‐oxidative acting transition metal ions (e.g. Fe) in α‐acid‐complexes during the whirlpool rest and fermentation. Consequently, fewer reactive oxygen species are generated. Additional laboratory trials simulating wort cooling and beer storage in buffered model solutions proved that un‐isomerized α‐acids are strong iron chelators and confirmed the functional principle of the applied hopping regimes. Negative effects of higher α‐acid contents on fermentation performance and depletion of the zinc concentration, which is an essential nutrient for yeast, could be excluded. Copyright © 2014 The Institute of Brewing & Distilling